Childhood Disturbances - Ahmed, Anjum (THE PRIMARY TEACHER, 2009)
Most children exhibit behaviour that may be seen as problematic at sometime or the other. This does not mean that they all have psychological problems and would always need serious professional help. It is necessary for us to understand as to when the problem can be handled by oneself or decide that the child is mentally or emotionally disturbed and requires help. In addition, one also needs to know what are the causes of these problems and the way in which a parent, a teacher or a doctor can help. The article, first elaborates the causes and kinds of childhood disturbances briefly describing its types with special consideration to psychological disturbances. Lastly, it highlights the remedial measure that can be taken to reduce, minimise or to eliminate to a large extent these disturbances